2022
DOI: 10.1302/2046-3758.113.bjr-2021-0350.r1
|View full text |Cite
|
Sign up to set email alerts
|

Do preoperative intra-articular injections of corticosteroids or hyaluronic acid increase the risk of infection after total knee arthroplasty? A meta-analysis

Abstract: Aims There is conflicting evidence on the safety of intra-articular injections of hyaluronic acid (HA) or corticosteroids (CSs) before total knee arthroplasty (TKA). We performed a meta-analysis of the relationship between intra-articular injections and subsequent infection rates after TKA. Methods We searched PubMed, EMBASE, and the Cochrane Library for cohort studies that assessed the effect of preoperative injection of drugs into the joint cavity on the infection rate after TKA. The outcomes analyzed includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Patient factors associated with postoperative infection in this study reflect the TKA literature, and include chronic obstructive pulmonary disease, chronic kidney disease, poorly controlled diabetes, obesity, liver disease, and smoking. 13,[18][19][20] Our multivariate analysis results for UKA reflect more recent TKA literature from Bhattacharjee et al who found no association between CSI performed from 2 weeks to 6 months prior to TKA. Interestingly, the authors did find CSI less than 2 weeks prior to TKA was an independent risk factor for postoperative infection (OR: 2.89; p ¼ 0.04).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Patient factors associated with postoperative infection in this study reflect the TKA literature, and include chronic obstructive pulmonary disease, chronic kidney disease, poorly controlled diabetes, obesity, liver disease, and smoking. 13,[18][19][20] Our multivariate analysis results for UKA reflect more recent TKA literature from Bhattacharjee et al who found no association between CSI performed from 2 weeks to 6 months prior to TKA. Interestingly, the authors did find CSI less than 2 weeks prior to TKA was an independent risk factor for postoperative infection (OR: 2.89; p ¼ 0.04).…”
Section: Discussionsupporting
confidence: 86%
“…Patient factors associated with postoperative infection in this study reflect the TKA literature, and include -COPD, CKD, poorly controlled diabetes, obesity, liver disease, and smoking 13,18,19,20 . Our multivariate analysis results for UKA reflect more recent TKA literature from Bhattacharjee et al who found no association between CSI performed from 2 weeks to 6 months prior to TKA.…”
Section: Discussionmentioning
confidence: 98%
“…A large database study by Cancienne et al, however, had a limitation in that the database was confined to a Medicare-only population [ 15 ], making it difficult to apply their results to the younger population [ 4 ]. Recent meta-analyses did not distinguish injected medications in assessing the risk of PJI [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies included patients who underwent knee joint arthroplasty and patients who underwent hip joint arthroplasty together in assessing the risk of PJI [ 20 22 ]. Some authors did not specify medications injected into the joint (corticosteroid, hyaluronic acid, or others) [ 23 , 24 ]. The previous studies have investigated the risk of PJI in the setting of various time intervals (from 4 weeks to 1 year) between preoperative injections and arthroplasty [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al reported that intra-articular injections of corticosteroid or hyaluronic acid prior to TKA increased the risk of postoperative infection. Injections given more than 3 months prior to TKA did not substantially augment the risk of infection [ 62 ].…”
Section: Discussionmentioning
confidence: 99%